Renewable energy: biogas and electricity from pig and cattle waste in UFSM - Pereira, Murilo Sagrillo; Godoy, Taís Pentiado; Godoy, Leoni Pentiado; Bueno, Wagner Pietrobelli; Wegner, Roger da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Biomass is biological mass or organic matter produced by decomposition of organic materials such as manure, agricultural waste and even remains of foods, among others. In this sense, there is a growing interest in preserving the environment through sustainability. Enterprises of all economic sectors are prioritizing investments in energy production from renewable sources, even if the return is not high in the short term, the case of environmental investments. Considering that the Federal University of Santa Maria (UFSM) has all the necessary support so there is a quality management in this sector, this research proposes to quantify possible energy potential of waste generated by pigs, beef cattle and dairy cattle UFSM, they want it, with the help of bibliographic references, get the theoretical biogas production by a digester, in optimal conditions, as well as the conversion of this amount into electrical energy unit.